When performance melts away: Heat causes mental errors in high-stakes competitions - Mario Lackner; Hendrik Sonnabend (Johannes Kepler University of Linz, Department of Economics, 2024)
This paper examines the impairing effect of heat stress on cognitive abilities in a high-stakes setting. Building on rich play-by-play data from the National Football League (NFL) linked to variations in game-time temperature, we find that players are about 25% more likely to be sanctioned for infractions associated with mental errors in games with temperatures above 85êF (29.4êC) compared to games with lower temperatures. Furthermore, we identify situations with (i) little room to adapt to heat stress and (ii) high work intensities, as well as the players' physical constitution as channels that can explain the heat-induced decline in mental performance.
Keywords: Q51; J24; J81; 330; heat stress; mental performance; football